Respiratory Manifestations of COVID-19 in Children: A Narrative Review - Farzad Masiha; Abbas Dabbaghzadeh; Negar Ghaffari; Javad Ghaffari (Mazandaran University of Medical Sciences, 2022)
Background: Coronavirus disease 2019 (COVID‐19, the seventh coronavirus) is a new infectious disease that spread worldwide and rapidly became a pandemic. COVID‐19 is rare in children and often asymptomatic. The respiratory system is mainly involved in COVID-19 infection.  Objectives: This study aimed to review respiratory manifestations in children with COVID-19. Methods: We searched for studies published from January 2020 to January 2021 in PubMed, Google Scholar, and Scopus in English. The search words were "2019-nCoV," "novel coronavirus," "COVID-19," "SARS-CoV-2," "severe acute respiratory syndrome coronavirus 2," "children," "child," "infant," "teenager," "adolescent," "pediatric," and "neonate." Results: Cough was a common symptom in our study (18.8%-100%, mean=64%). Pneumonia prevalence in children with COVID-19 is 11%-67% (mean=46%). Mild respiratory symptoms (14% - 60%) and severe respiratory distress syndromes (14%) were reported in some studies. Upper respiratory tract infection (URTI) was reported in 4 studies ranging from 11.1% to 34.4% (mean=24.1%). Ground-glass opacities (GGO) was reported in 12.2% to 81% of cases (mean=49.01%). Isolated consolidations were reported in 17% and 58% of patients in two studies. Enhanced lung texture was reported in 1.3% to 50% (mean=20.07%) of patients. Bilateral patchy shadowing was seen in 12.3% to 68% (mean=46.58%) of patients. Conclusions: Cough is the most common manifestation of respiratory system involvement in children with COVID-19. GGO and bilateral patchy involvement are the most common finding on lung CT scans in children with COVID-19.